Prone positioning in mechanically ventilated patients with severe acute respiratory distress syndrome and coronavirus disease 2019. Issue 3 (22nd November 2020) - Gleissman, Helena; Forsgren, Anders; Andersson, Elisabeth; Lindqvist, Elin; Lipka Falck, Adam; Cronhjort, Maria; Dahlberg, Martin; Günther, Mattias
Abstract: Background: The management of COVID‐19 ARDS is debated. Although current evidence does not suggest an atypical acute respiratory distress syndrome (ARDS), the physiological response to prone positioning is not fully understood and it is unclear which patients benefit. We aimed to determine whether proning increases oxygenation and to evaluate responders. Methods: This case series from a single, tertiary university hospital includes all mechanically ventilated patients with COVID‐19 and proning between 17 March 2020 and 19 May 2020. The primary measure was change in PaO2 :FiO2 . Results: Forty‐four patients, 32 males/12 females, were treated with proning for a total of 138 sessions, with median (range) two (1‐8) sessions. Median (IQR) time for the five sessions was 14 (12‐17) hours. In the first session, median (IQR) PaO2 :FiO2 increased from 104 (86‐122) to 161 (127‐207) mm Hg ( P < .001). 36/44 patients (82%) improved in PaO2 :FiO2, with a significant increase in PaO2 :FiO2 in the first three sessions. Median (IQR) FiO2 decreased from 0.7 (0.6‐0.8) to 0.5 (0.35‐0.6) (<0.001). A significant decrease occurred in the first three sessions. PaO2, tidal volumes, PEEP, mean arterial pressure (MAP), and norepinephrine infusion did not differ. Primarily, patients with PaO2 :FiO2 approximately < 120 mm Hg before treatment responded to proning. Age, sex, BMI, or SAPS 3 did not predict success in increasing PaO2 :FiO2 . Conclusion: Proning increased PaO2 :FiO2, primarily in patients with PaO2 :FiO2 approximately < 120 mm Hg, with a consistency over three sessions. No characteristic was associated with non‐responding, why proning may be considered in most patients. Further study is required to evaluate mortality.